Using Combined Bipolar Semantic Scales and Eye‐Tracking Metrics to Compare Consumer Perception of Real and Virtual Bottles. (December 2015) - Rojas, Juan‐Carlos; Contero, Manuel; Bartomeu, Noemí; Guixeres, Jaime
Abstract : Three‐dimensional virtual representations of consumer products are expected to gain relevance in e‐commerce applications as low cost virtual reality headsets arrive on the market in the next years. However, there are a limited number of studies related to the perceptual evaluation of virtual products and their packaging where virtual and real (photographic) representations are compared. As part of an extensive exploration toward understanding product perception in virtual stores, this work presents a study with 38 participants in which consumer perceptions of a photographic and a virtual representation of a beer bottle are examined. Perceptual evaluation is assessed using two metrics: first, an evaluation was performed by applying a bipolar semantic scale based on four axes: novelty, resolution, style and emotion. Second, eye‐tracking metrics were employed to analyse participant gaze behaviour during the visualization of stimuli. Virtual bottles were modelled using a medium polygonal load (5 K polygons per bottle), and render quality was also medium to intentionally recreate the computing limitations of smartphone‐based virtual reality headsets. Results show that a medium render quality alters consumer perception and responses using semantic scales. Eye‐tracking analysis confirms that the orientation of the bottle and how it is presented also affect consumer perception. While some orientations result in similar eye‐tracking metrics, others show different results. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : This work presents a study with 38 participants in which consumer perceptions of a photographic and a virtual medium quality representation of a beer bottle are examined. Results show that a medium render quality alters consumer perception and responses using semantic scales. Eye‐tracking analysis confirms that the orientation of the bottle and how it is presented also affects consumer perception.